Pengaruh Model Pembelajaran Kooperatif Tipe Time Token terhadap Hasil Belajar Fisika Siswa - Fifiyanti; Amiruddin Hatibe; I Wayan Darmadi (Jurnal Kreatif Online, 2021)
This study aims to see whether there is an effect of the time token type cooperative learning model on the physics learning outcomes of seventh grade students of SMP Negeri 1 Banawa Tengah. The type of research used is a quasi-experimental design with "the non-equivalent pretest-posttest group design". The sample was selected using purposive sampling technique. Class VII B as the control class and class VII D as the experimental class. The instrument used is a test of physics learning outcomes in the form of multiple choice that has been tested and data analysis techniques. Based on the results of data processing, for the experimental class, the average final test score was 8.80 with a standard deviation of 3.30. For the control class, the average final test score was 6.10 with a standard deviation of 3.11. The results of hypothesis testing obtained tcount = 3.43 and ttable = 2.02. This means that the value of tcount is outside the H0 acceptance region. These results provide an opportunity to state that there are differences in physics learning outcomes between the control class and the experimental class. Thus, it can be concluded that there is an effect of the time token type of cooperative learning model on the physics learning outcomes of seventh grade students of SMP Negeri 1 Banawa Tengah.